Pelaksanaan Penilaian Berbasis Kelas dalam Pembelajaran Bahasa Indonesia Pada Mts. Swasta Madrasah Ulumul Quran Kota Langsa - Joko Hariadi (Program Studi Pendidikan Sejarah - Universitas Samudra, 2016)
The research problem is how the implementation of the class-based assessment on Indonesian study subjects at MTs. MUQ Kota Langsa. The purpose of this study was to describe the implementation of the class based assessment on Indonesian study subject at MTs. MUQ Kota Langsa. This research is qualitive descriptive research, while the collection techniqoes are 1. Observation 2. Interview 3. Recording 4. Documentation. From the observation that researcher do, in the learning plan, the teachers, make a RPP. After a well structured learning plan, the teachers are teaching and learning activities according the plan. The next step, the teachers implementation of implemeting assessment phase which conducted on the overall value for one semester, and as well as on every aspects of product assessment and performance assessment. Product assessment can provide an apportunity to the students to competence by him self than the others. So as to obtain a real understanding than he doing by him self. During implementation of performance assessment on indonesian study subject, the learning out comes could be success, because basicly on the implementation of performance assessment many alternative forms of matter which could be used by the teachers in accordance with the matter. Conclusions from the implementation of PBK on the product assessment and performance assessment has met the minimum completeness criteria. Because in implementation of PBK, we could see that the students activity againt the assignment of teachers very good from the learning performance till doing the task which has given by teachers.the research suggest should the head master coordinate with the langsa city government in order to give more attention and greater support to the Indonesian subject teacher to successing of the implementation of class based assessment with disseminating the results of the workshop and seminar about the implementation of class based assessment especially for Indonesian subject and provide guldance for the teacher about implementation of the class based assessment.